Comparative method between electrocoagulation and ozonolysis for sulphide removal - Nor Hidayah, Nordin (2017)
Sulphide is one of the example of contaminants contains in industries and give harmful effect to human, plant, and environment. High amount of sulphide content contributed to corrosion of pipe in industries. In this research, it was intended to develop the new technologies by using comparison between Ozonolysis and Electrocoagulation (EC) method that will give the highest percentage of Sulphide removal. The experiment was carried out in batch reactor and conducted under galvanostatic regime at current 1A and the voltage supply was 30V. Both of methods were run in 0.8L of sample solutions which were stock sulphide and sample from MTBE companies. Concentrations of both samples at influent were varied at (50,100,150 and 200) ppm. EC process involved Iron electrodes where arrangements of electrodes monopolar-parallel (M-P) and bipolar-parallel (B-P) were investigated in this research. By weighing both the electrode before and after electrocoagulation and based on Faraday’s law, weight of precipitated were determined. Ozone injection during ozonolysis was 10% for all trials. Solutions had been used in both method were taken at regular times at (3, 6, 9, 12, and 15 minutes) to measure Sulphide removal while (15, 30, 45, and 60 minutes) for COD removal. Then, percentage of Sulphide removal was calculated and efficiency of COD removal was evaluated. In ozonolysis, 98.97% of sulphide removal had achieved by using sample from MTBE, while only 48.48% sulphide removal used in stock sulphide. The arrangement of B-P electrode had achieved 77.57% and 84.87% of Sulphide and COD removal, while in monopolar only 40% and 78.64%of Sulphide and COD removal respectively. In conclusion, sample from MTBE gave the high quality in removal of Sulphide in ozonolysis treatment, and B-P arrangement was the best position to determine the highest percentage of Sulphide removal in electrocoagulation.